Analysis of the source of heterogeneity in the osmotic response of plant membrane vesicles - Alleva, Karina (2008)
Plasma membrane vesicles have been widely employed to understand the biophysics of water movements, especially when active aquaporins are present. In general, water permeability coefficients in these preparations outcome from the analysis of the osmotic response of the vesicles by means of light scattering. As from now, this is possible by following a theoretical approach that assumes that scattered light follows a single exponential function and that this behavior is the consequence of vesicle volume changes due to an osmotic challenge. However, some experimental data do not necessarily fit to single exponentials but to double ones. It is argued that the observed double exponential behavior has two possible causes: different vesicle population in terms of permeability or in terms of size distribution. As classical models cannot identify this source of heterogeneity, a mathematical modeling approach was developed based on phenomenological equations of water transport. In the three comparative models presented here, it was assumed that water moves according to an osmotic mechanism across the vesicles, and there is no solute movement across them. Interestingly, when tested in a well described plasma membrane vesicle preparation, the application of these models indicates that the source of heterogeneity in the osmotic response is vesicles having different permeability, clearly discarding the variable size effect. In conclusion, the mathematical approach presented here allows to identify the source of heterogeneity; this information being of particular interest, especially when studying gating mechanisms triggered in water channel activity.